Evaluation of the automicrobic system for detection of resistance of Staphylococcus aureus to methicillin. - Woolfrey, B F (1984)
The AutoMicrobic system (AMS) (Vitek System, Inc., Hazelwood, Mo.) was tested for its ability to determine oxacillin and gentamicin susceptibility of 98 known oxacillin-susceptible and 103 known oxacillin-resistant Staphylococcus aureus isolates. AMS and reference oxacillin susceptibility results were in agreement for all 95 (100%) oxacillin-susceptible isolates. In contrast, only 23 (22.3%) of the 103 known oxacillin-resistant isolates were correctly reported. For the known oxacillin-resistant isolates, 65 received AMS reports at 3 to 4 h, with only 9% being correct, whereas 38 were reported at 5 to 6 h, with 47% being correct. The reliability of AMS gentamicin susceptibility results was evaluated by testing the 198 S. aureus isolates in parallel with MIC-2000 broth dilution tests. AMS gentamicin susceptibility results were found to be reliable and essentially identical to MIC-2000 results. The possibility of improving AMS oxacillin resistance detection by using gentamicin resistance as a linked screening marker for oxacillin resistance was evaluated with data from the parallel AMS and MIC-2000 gentamicin susceptibility tests and from data accrued on recent clinical laboratory isolates. By these two approaches, respective sensitivities of 97 and 99.8%, and specificity of 72%, were found for detection of oxacillin-resistant isolates by using gentamicin resistance as a marker.